SUICIDAL IDEATION, DEPRESSION, ANXIETY, STRESS, AND LIFE SATISFACTION OF MEDICAL, ENGINEERING, AND SOCIAL SCIENCES STUDENTS - Naseem, Sabahat; Munaf, Seema (Journal of Ayub Medical College Abbottabad, 2017)
Background: Pursuing higher education is not an easy task as it requires hard work, dedication, and motivation. Although there are many rewards involved in growing up academically, nevertheless, it contains a few hazards too. For instance, suicidal ideation is associated with presence of depression, anxiety, and stress with low level of satisfaction with life in students finding difficulty in handling educational demands of higher education. Therefore, the present study focused on the query that whether there is any difference or not among medical, engineering, and social sciences students of city of Karachi, Pakistan in the level of suicidal ideation, depression, anxiety, stress, and life satisfaction. Methods: Using comparative group design, total 300 students (150 males and 150 females) with age range of 19-26 were selected from faculties of medical, engineering, and social sciences of different universities of Karachi, Pakistan, through purposive sampling. Respondent Profile Form, The Suicide Behaviours Questionnaire-Revised, Depression Anxiety Stress Scale-21, and Satisfaction with Life Scale were administered to assess suicidal ideation; depression, anxiety, stress; and life satisfaction, respectively, of the students. Scores were analysed through ANOVA and Post Hoc (Tukey’s HSD) test using SPSS. Results: Social sciences and engineering students were significantly higher on depression, anxiety, and stress than medical students [F (2, 297) =8.701, p=.000] whereas insignificant differences in the level of suicidal ideation [F (2, 297) =1.914, p=.149] and life satisfaction [F (2, 297) = .726, p = .485] among these students were found. Conclusion: With the help of these findings, it would be easier to counsel students of different disciplines in time on the lines of suggested preventive measures. Keywords: Suicidal ideation; Depression; Anxiety; Stress; Life Satisfaction; Students